Membangun Komunitas Entrepreneur Muda Pada Pondok Pesantren DDI Ujung Lare Parepare - Nur, Nikmatullah; A. Rio Makkulau; Anwar, Wirani Aisiyah (Dharma: Jurnal Pengabdian Masyarakat, 2024)
This form of Community Service is a community service program carried out to be able to develop the entrepreneurial potential of students at the DDI Ujung Lare Islamic Boarding School so that they have life skills as capital for life in the midst of society using the MBPM (Making, Branding, Packaging, and Marketing) Model. It is hoped that they will be able to develop the entrepreneurial potential of students at the DDI Ujung Lare Islamic Boarding School so that they have life skills as capital for living in society. This activity aims to build a community of young entrepreneurs at the DDI Ujung Lare Parepare Islamic Boarding School with the aim of empowering students with entrepreneurial skills. Through this program, students will be given training and guidance in various aspects of business, from planning to marketing. This initiative not only aims to create jobs for students after they graduate, but also to foster a spirit of independence and innovation within the Islamic boarding school community. By creating an ecosystem that supports entrepreneurship, it is hoped that students can become agents of change who contribute positively to the regional and national economy. This program also aims to create new jobs and improve the welfare of the community around the Islamic boarding school. Through continuous development and collaborative networks, it is hoped that this young entrepreneurial community will be able to develop and have a significant long-term impact. Thus, it is hoped that this service activity can make a positive contribution to the local economy and improve the welfare of the surrounding community